2018
DOI: 10.1590/s1517-707620170001.0301
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured titanium dioxide average size from alternative analysis of Scherrer's Equation

Abstract: RESUMOQuantificar o tamanho de materiais em escala nanométrica é um dos desafios a serem superados, uma vez que existem técnicas diferentes. A equação de Scherrer modificada foi usada para estimar o tamanho das partículas de dióxido de titânio em escala nanométrica. Dióxido de titânio com tamanho nominal de nanopartícu-la de 21 nm foi usado como padrão para determinar a precisão da equação modificada. A partir dos dados de raios-X, para a amostra sem tratamento térmico foi obtido um valor médio do tamanho das … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Using XRD data, it was also possible to calculate the average crystallite size for the different crystalline planes of RuO 2 and TiO 2 , using the Scherrer equation [ 31 ]: D = 0.9 × λ/β × cos θ β where D is the average size of the crystallite, λ the wavelength of the radiation, β the width of the reflection in radians and θ β the angle of maximum intensity of the reflection. The results are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Using XRD data, it was also possible to calculate the average crystallite size for the different crystalline planes of RuO 2 and TiO 2 , using the Scherrer equation [ 31 ]: D = 0.9 × λ/β × cos θ β where D is the average size of the crystallite, λ the wavelength of the radiation, β the width of the reflection in radians and θ β the angle of maximum intensity of the reflection. The results are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…For the crystallinity studies done using XRD, as shown in Figure 4 , the major peaks were at 2θ values of 25.18° (101), 37.73° (004), 47.94° (200), 53.76° (105), and 54.96° (211), which indicated the successful synthesis of anatase TiO 2 NP S. The XRD pattern confirmed the synthesized TiO 2 consist of anatase phase in high purity, with average crystallite size in the range of 19–21 nm. Scherer's equation (Lima et al, 2018 ), which relates the size of sub-micrometer crystallites in a solid to broadening of a sample peak in a diffraction pattern' illustrated as; D = K λ / β cos θ where ( D ) is average crystal size for the main broadening anatase peak; K = Scherrer's coefficient constant (0.89) which depend on the crystallite shape, λ = X-ray wavelength; β = full width at half maximum intensity (FWHM) of diffraction peaks in radians and θ = Bragg's angle, has been used to correlate the sample analysis reference pattern. The average crystallite size of the synthesized TiO 2 was 11 nm, which showed similarity with TiO 2 NPs synthesis using the extracts of Syzygium cumini , as reported by Sethy et al ( 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The crystallite average size (D) of the anatase TiO (Table 1) and monoclinic WO in the investigated 𝑇𝑊, 𝑇𝑊 − 𝑍𝑛2 and 𝑇𝑊 − 𝑍𝑛4 nanocomposites was determined by the modified Scherrer equation (MSE), D = λ 3βcos (θ) ⁄ [24], where 1/3 is the correction value of the shape factor K in Scherrer Equation [25]; λ is the X-ray radiation wavelength; β and θ are the full width half maxima and the half of the diffraction angle (2θ) at the crystal planes detected in the XRD spectrum, respectively. In fact, there is the occurrence of zinc ion doping in the atomic structure of titanium: the ionic radius of Zn 2+ ions (0.74 Å [23]) is close to that of Ti 4+ ions, promoting the occupation of vacancies of the Ti atom sites by Zn elements, after the sintering process.…”
Section: Microstructural Analysismentioning
confidence: 99%
“…The crystallite average size (D) of the anatase TiO 2 (Table 1) and monoclinic WO 3 in the investigated TW, TW − Zn2 and TW − Zn4 nanocomposites was determined by the modified Scherrer equation (MSE), D = λ/3β cos(θ) [24], where 1/3 is the correction value of the shape factor K in Scherrer Equation [25]; λ is the X-ray radiation wavelength; β and θ are the full width half maxima and the half of the diffraction angle (2θ) at the crystal planes detected in the XRD spectrum, respectively.…”
Section: Microstructural Analysismentioning
confidence: 99%